2022
DOI: 10.1186/s12967-022-03604-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Omega-3 fatty acids supplementation on serum level of C-reactive protein in patients with COVID-19: a systematic review and meta-analysis of randomized controlled trials

Abstract: Background Omega-3 may alleviate the severity of coronavirus disease 2019 (COVID-19) by reducing the C-reactive protein (CRP) level, a marker for systemic inflammation. Because the scientific evidence indicating such a role is inconsistent, we aimed to evaluate the effect of Omega-3 on CRP change and CRP level in patients with COVID-19. Methods We conducted a comprehensive search on four databases (PubMed, Web of Science, EMBASE, and Scopus). We in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…DHA could be metabolized by macrophages to produce d -series dissolution, maresin, and protective protein, which can inhibit the secretion of inflammatory factors by macrophages, induce anti-inflammatory transformation and promote efferocytosis. , Therefore, we introduced DHA into the biomimetic hybrid nanovesicles ANeu-DDAB, to play an excellent anti-inflammatory and pro-resolution synergistic effect. First, we explored the effects of different DHA dosages on the particle size, zeta potential, drug loading capacity, and encapsulation efficiency of ANeu-DDAB.…”
Section: Resultsmentioning
confidence: 99%
“…DHA could be metabolized by macrophages to produce d -series dissolution, maresin, and protective protein, which can inhibit the secretion of inflammatory factors by macrophages, induce anti-inflammatory transformation and promote efferocytosis. , Therefore, we introduced DHA into the biomimetic hybrid nanovesicles ANeu-DDAB, to play an excellent anti-inflammatory and pro-resolution synergistic effect. First, we explored the effects of different DHA dosages on the particle size, zeta potential, drug loading capacity, and encapsulation efficiency of ANeu-DDAB.…”
Section: Resultsmentioning
confidence: 99%
“…The second lipid-lowering drug that was investigated in two trials is omega-3. Supplementation with omega-3 reduces systemic inflammation in SARS-CoV-2 infection by reducing the CRP levels [ 38 ]. Moreover, blood levels of omega-3 were lower in more severe forms of COVID-19 [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Omega-3 supplementation was found to have promising effects on acidosis and renal function, possibly improving clinical outcomes in SARS-COV-2 patients ( 51 ). a systematic review and meta-analysis of randomized controlled trials on the effect of Omega-3 fatty acids supplementation in patients with SARS-COV-2 have reported that Omega-3 supplementations have been associated with alleviating the inflammatory response by the CRP level reduction ( 52 ).…”
Section: Lipidmentioning
confidence: 99%